Applied thematic analysis - Guest, Greg 1963-; MacQueen, Kathleen M.; Namey, Emily E. (Sage Publications, 2012)
"This book provides step-by-step instructions on how to analyze text generated from in-depth interviews and focus groups - i.e., transcripts. The book is primarily designed for research studies with an applied focus, but is also useful for theoretically oriented qualitative research. The book covers all aspects of the qualitative data analysis process including planning, data preparation, identification of themes, codebook development and code application, reliability and inter-coder agreement, data reduction techniques, comparative techniques, integration with quantitative data, and software considerations. The book describes what the authors call "applied thematic analysis", because it is the approach predominantly used in applied qualitative studies (and increasingly in academic contexts). The method employs a phenomenological approach to data analysis which has a primary aim of describing the experiences and perceptions of research participants. The approach presented is similar to Grounded Theory - in that it is inductive, content-driven, and searches for themes within textual data - and is complementary to Grounded Theory on many levels. However, within an applied context a phenomenological approach is primarily concerned with characterizing and summarizing perceptions and lived experiences and applying the results to a particular research problem, rather than building and assessing theoretical models"--Provided by publisher.